A preservação da memória da vila Santa Thereza em Bagé RS/Brasil, a partir do audiovisual e das ações da sociedade civil - Ferreira, Adriana Gonçalves (2020)
This study a im stoverify the importance of audiovisual in the preservation of memory and heritage. To this end, we study the village of Santa Thereza in Bagé RS, valuing the actions of organized civil society and its struggle for the preservation of this cultural heritage. Presents a study that attentive to the community that in habits this village and its report sthrough the orality captured in documentary film format. It is the purpose of this research, in the context of audiovisual production, to conceive it in a collective process, leading the local actors them selves, through the pedagogical practices of the project “invent with Difference”, which unites cinema, education and human rights, issues that hus like heritage, are present every where. It looks at how audiovisual production can be considered a museum the memory. The work permeates the trajectory of Associação Pró Santa Thereza, a collective of voluntary women that protects the heritage and inspires ways of pointing paradigms in society, in the context of hypermodernity. It presents a trace of the history of Vila de Santa Thereza, which arises with the founding of a Charqueada at the end of the 19th century, founded in 1897 by a Portuguese immigrant named Antônio Nunes de Ribeiro Magalhães, until there signification of space and your survival. The work observes there main ingresidents of charqueada, realizing the importance of individual and collective memory in that space and its recognition as heritage. At the time, the rewas a cultural and religious life through the actions carried out at the Santo Antônio The aterand Santa Thereza D'Avila Chapel, which were part of the complex built around the jerked beef business. Work, culture, and religiosity drove an active community life thats hared attention with the city of Bagé, the State, and Brazil until the end of the charque's economic cycle in 1960. There after, more than 30 years of oblivion, this space reappears at the hands of the arduous volunteering of this Association.